2012
DOI: 10.1111/j.1365-2125.2011.04137.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the pharmacology and tolerability of PF‐04457845, an irreversible inhibitor of fatty acid amide hydrolase‐1, in healthy subjects

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Inhibition of fatty acid amide hydrolase‐1 (FAAH1) and the subsequent elevation of fatty acid amides has been proposed as a strategy to induce the analgesic properties of cannabinoids without the accompanying negative side effects such as impairment in cognition, motor control and predisposition to psychoses. PF‐04457845 is a potent and selective irreversible FAAH1 inhibitor which has been shown to elevate fatty acid amide concentrations in animal models and induce re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 25 publications
(37 reference statements)
6
93
0
Order By: Relevance
“…A recent study using a 4 mg once‐daily dose of the selective FAAH inhibitor PF‐04457845 demonstrated clinical efficacy in patients suffering from cannabis use disorder (CUD) in terms of reduced cannabis withdrawal symptoms, cannabis use, and sleep disturbances 17. This dose had been previously shown to be more than sufficient to result in 97% inhibition of WBC FAAH and elevate plasma FAAs 18. Dose ranging was not done, so these clinical results can only suggest that complete inhibition of FAAH is necessary for efficacy, at least in CUD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using a 4 mg once‐daily dose of the selective FAAH inhibitor PF‐04457845 demonstrated clinical efficacy in patients suffering from cannabis use disorder (CUD) in terms of reduced cannabis withdrawal symptoms, cannabis use, and sleep disturbances 17. This dose had been previously shown to be more than sufficient to result in 97% inhibition of WBC FAAH and elevate plasma FAAs 18. Dose ranging was not done, so these clinical results can only suggest that complete inhibition of FAAH is necessary for efficacy, at least in CUD.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were reminded to have a light meal in the morning and a light lunch was permitted between the scans as food is known to have little effect on overall PF-04457845 pharmacokinetics. 25 …”
Section: Pf-04457845 Dosing Regimenmentioning
confidence: 99%
“…PF-04457845 is a highly potent (IC 50 = 7.2 nmol/L, with k inact /K i = 40,300/M/s, where k inact is the first-order rate constant of enzyme inactivation at infinite inhibitor concentration and K i is the inhibitor dissociation constant) 23,24 and highly specific irreversible FAAH inhibitor in vitro and ex vivo based on the extensive preclinical characterization. In human clinical trials, 25 this investigational drug was shown to have good safety and tolerability profile and inhibited FAAH activity in peripheral blood leukocytes (497% at 0.3 mg, p.o.) and increased plasma concentrations of fatty acid amides by 3.5 to 10 fold although its effectiveness and optimal dose regimen in the living human brain is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…5A), a FAAH inhibitor with excellent potency, selectivity, oral availability, and efficacy in a rat models of inflammatory and noninflammatory pain (Ahn et al, 2011;Johnson et al, 2011). In phase I trials, PF-04457845 nearly completely inhibited FAAH activity in blood leukocytes, elevated plasma anandamide and other NAE levels 3.5-to 10-fold, and was well tolerated (Li et al, 2012). Recently, however, PF-04457845 failed to show efficacy in Phase II trials in patients with osteoarthritic knee pain .…”
Section: A Faah Inhibitorsmentioning
confidence: 99%